Discharge Information and Support for Patients Discharged from the Emergency Department: Results from a Randomized Controlled Trial - Hastings, Susan N. (J Gen Intern Med, 2019)
BACKGROUND: Little research has been done on primary care–based models to improve health care use after an emergency department (ED) visit. OBJECTIVE: To examine the effectiveness of a primary care–based, nurse telephone support intervention for Veterans treated and released from the ED. DESIGN: Randomized controlled trial with 1:1 assignment to telephone support intervention or usual care arms (ClinicalTrials.gov: NCT01717976). SETTING: Department of Veterans Affairs Health Care System (VAHCS) in Durham, NC. PARTICIPANTS: Five hundred thirteen Veterans who were at high risk for repeat ED visits. INTERVENTION: The telephone support intervention consisted of two core calls in the week following an ED visit. Call content focused on improving the ED to primary care transition, enhancing chronic disease management, and educating Veterans and family members about VHA and community services. MAIN MEASURES: The primary outcome was repeat ED use within 30 days. KEY RESULTS: Observed rates of repeat ED use at 30 days in usual care and intervention groups were 23.1% and 24.9%, respectively (OR = 1.1; 95% CI = 0.7, 1.7; P = 0.6). The intervention group had a higher rate of having at least 1 primary care visit at 30 days (OR = 1.6, 95% CI = 1.1–2.3). At 180 days, the intervention group had a higher rate of usage of a weight management program (OR = 3.5, 95% CI = 1.6–7.5), diabetes/nutrition (OR = 1.8, 95% CI = 1.0–3.0), and home telehealth services (OR = 1.7, 95% CI = 1.0–2.9) compared with usual care. CONCLUSIONS: A brief primary care–based nurse telephone support program after an ED visit did not reduce repeat ED visits within 30 days, despite intervention participants’ increased engagement with primary care and some chronic disease management services. TRIALS REGISTRATION: ClinicalTrials.gov NCT01717976.